2017
DOI: 10.1042/bcj20160499
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding proteins with prion-like domains in health and disease

Abstract: Approximately 70 human RNA-binding proteins (RBPs) contain a prion-like domain (PrLD). PrLDs are low-complexity domains that possess a similar amino acid composition to prion domains in yeast, which enable several proteins, including Sup35 and Rnq1, to form infectious conformers, termed prions. In humans, PrLDs contribute to RBP function and enable RBPs to undergo liquid–liquid phase transitions that underlie the biogenesis of various membraneless organelles. However, this activity appears to render RBPs prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
424
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(447 citation statements)
references
References 248 publications
(511 reference statements)
7
424
0
1
Order By: Relevance
“…We confirmed that this loss of yTRAP signal for Hrp1 and another top candidate, Ngr1, was accompanied by microscopic foci formation (Figure 6B). Hrp1 is the closest yeast homolog of human hnRNPA1, the aggregation of which is associated with both MSP and ALS (Harrison and Shorter, 2017). Thus, we decided to focus on Hrp1 for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that this loss of yTRAP signal for Hrp1 and another top candidate, Ngr1, was accompanied by microscopic foci formation (Figure 6B). Hrp1 is the closest yeast homolog of human hnRNPA1, the aggregation of which is associated with both MSP and ALS (Harrison and Shorter, 2017). Thus, we decided to focus on Hrp1 for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These genes are heavily enriched for RNA-binding and RNA-processing activity, including many aggregation-prone proteins associated with fatal neurodegenerative diseases (Harrison and Shorter, 2017). However, natural assemblies/aggregates of RNA-binding proteins (RBPs) are important for RNA storage, processing, and degradation (Protter and Parker, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that, at a molecular level, long-term memory is characterized by its requirement for changing the profiles of gene expression which is mainly implemented by the RNA-binding proteins with the prion-like domains (Shorter and Lindquist 2005;Rayman and Kandel 2017;Sudhakaran and Ramaswami 2017). However, even in the human genome, it is likely that there exist <240 RNA-binding proteins with the prion-like domains (Harrison and Shorter 2017). So how can such a limited number of the RNA-binding proteins produce a giant amount of the gene expression profiles to consolidate long-term memory and/or even more generally cellular memory?…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 99%
“…1f), which are enriched in polar and uncharged amino acids such as Gln, Asn, Ser, Gly and Tyr. As they share compositional similarity to the yeast prions such as Sup35, they are thus called Bprion-like^domains (Shorter and Lindquist 2005;Michelitsch and Weissman 2000;Chien and Weissman 2001;Han et al 2012;Harrison and Shorter 2017). Recently,~240 out of~20,000 human protein-coding genes (~1.2%) were shown to contain at least one prion-like domain, and, interestingly, human proteins containing the prion-like domains are over-represented by those critically interacting with RNA/DNA including TDP-43 and FUS proteins.…”
Section: Aggregation and Self-assembly Into Liquid Droplets And Fibrimentioning
confidence: 99%
See 1 more Smart Citation